Eribulin: clinical review and new perspective in advanced breast cancer - Gadekar, Arvind (International Journal of Advances in Medicine, 2021)
Eribulin is a unique microtubule inhibitor with mitotic and nonmitotic mechanisms of action. Eribulin has substantial activity in patients with pretreated (anthracycline and a taxane) advanced or metastatic breast cancer was confirmed by large-scale phase III clinical trials. We review recent pharmacological and clinical findings of eribulin use in metastatic breast cancer, particularly highlighting eribulin in difficult-to-treat and aggressive disease and safety data in specific patient populations. Furthermore, recent advancements and potential future directions for its clinical usage in our understanding are discussed. Ongoing studies of eribulin in combination with immunotherapies and established cytotoxic agents may facilitate to shape the future landscape in the treatment of breast cancer.